Hubungan Dukungan Keluarga dan Lama Menjalani Terapi Hemodialisa dengan Kualitas Hidup Pasien Gagal Ginjal Kronik di RST TK.III DR. Reksodiwiryo Padang - Fitria Alisa; Weny Amelia; Lola Despitasari; Ria Desnita; Lenni Sastra; Rahmi Syarmillah (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
Chronic kidney failure patients undergoing HD therapy will have effects such as blackened body, fatigue, nausea and vomiting so that their quality of life decreases. Family support can help improve the patient's quality of life. Patients who have been on HD therapy for a long time can finally accept the situation so that it will improve the quality of life. The purpose of this study was to determine the relationship between family support and duration of HD therapy with the quality of life of patients with chronic kidney failure at RST TK.III Dr. Reksodiwiryo Padang. This type of research is a cross sectional study. The sample in this study amounted to 45 samples with the